Potential of Biomass Briquettes from Tropical Fruit Waste (Study Case: Durian Skin) - Praditya S. A. Sitogasa; Mohamad Mirwan; Firra Rosariawari (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The search for alternative and sustainable renewable energy sources has become necessary as the world faces growing concerns over climate change and depleting fossil fuel reserves. Biomass briquettes, derived from various organic materials, present a promising solution to this global energy crisis. This study explores the potential of utilizing tropical fruit, specifically durian (Durio zibethinus), as a renewable energy source by producing biomass briquettes. Durian is a widely cultivated tropical fruit, abundant in certain regions but often underutilized due to its strong aroma and perishability. By converting durian waste into biomass briquettes, we can address environmental challenges while creating a valuable energy resource that aligns with sustainability principles.